2011
DOI: 10.1080/15245004.2010.546943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a County-Sponsored Social Marketing Campaign to Increase Mothers' Initiation of HPV Vaccine for Their Preteen Daughters in a Primarily Rural Area

Abstract: Routine vaccination against human papillomavirus (HPV), the main cause of cervical cancer, is recommended for 11-12 year old girls, yet vaccine uptake is low. This study evaluates a social marketing campaign initiated by 13 North Carolina counties to raise awareness among parents and reduce barriers to accessing the vaccine in a primarily rural area. The 3-month campaign targeted mothers of girls ages 11-12 and healthcare practices serving pre-teen girls in four counties. Principles of social marketing were: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 28 publications
0
79
0
Order By: Relevance
“…100,109 Additional intervention research is urgently needed to evaluate approaches for supporting effective provider communication and to prospectively evaluate the impact of those interventions on HPV vaccine uptake. Message testing to understand the impact of providers' communication content on parents' HPV vaccine decision making and satisfaction could be especially useful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…100,109 Additional intervention research is urgently needed to evaluate approaches for supporting effective provider communication and to prospectively evaluate the impact of those interventions on HPV vaccine uptake. Message testing to understand the impact of providers' communication content on parents' HPV vaccine decision making and satisfaction could be especially useful.…”
Section: Discussionmentioning
confidence: 99%
“…109 A second study evaluated a social marketing campaign that included public service announcements and the provision of clinic-based educational materials to parents of adolescents; most providers who participated reported that the campaign made them more likely to discuss and recommend HPV vaccination. 100 …”
Section: Visit Typementioning
confidence: 99%
See 2 more Smart Citations
“…75 Its concepts include components of several health behavior theories, social psychology, marketing science, and communication research. The application of social marketing to adolescent vaccination was explored by Cates and colleagues 76,77 in two studies. In the first, social marketing principles were used to design educational materials about HPV vaccination targeted to mothers of 11-12-year-olds and distributed across four counties in North Carolina.…”
Section: Population-level Interventionsmentioning
confidence: 99%